BAHASA KIASAN DALAM PUISI-PUISI KARYA CARL SANDBURG - ALOTIA, HAKRYAN (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT Â  This study which is entitled â€œFigurative Language in Carl Sandburg Poemsâ€ focusing on the use of a figurative language and categorize it accordance with the types and describe the meaning of figurative language itself. The writer chooses five poems which have interesting titles and famous works of Carl Sandburg and using content analysis method with intrinsic approach to gain an understanding of the meaning of figurative language in each poem. The purpose of this study was to identify and categorize the types of figurative language and analyzing and explaining the meaning of figurative language used Carl Sandburg in his poems. This study uses the theory of Perrine (1983: 576-645), in his book â€œLiterature, Structure, Sound and Senseâ€. According to Perrine, figurative language is a way to express something beyond the usual way. In his book also describes the types of figurative language such as personification, metaphors, similes, symbols, synecdoche, metonymy, and hyperbole. The results of the study can be summarized as follows : first, in the poems of Carl Sandburg, there are seven types of figurative language, including : personification, metaphor, symbol, similitude, metonymy, hyperbole, and synecdoche. The metaphors and personification types dominate every poem of Carl Sandburg. Second, the meaning of figurative language used by Carl Sandburg in his poems in general described the poetâ€™s admiration of the existence and role of the people and the relationship between the people and the government in a city or country. Keywords : Poems, Figurative Language, Carl Sandburg Â